Si︠e︡vernai︠a︡ chastʹ Okhotskago mori︠a︡ otʺ g. Okhotska do mysa Aregicheinskago po opisi Gidrograficheskoĭ Ėkspedt︠s︡īi Vostochnago okeana sʺ 1908 po 1914 godʺ / Sostavli︠a︡li i chertili Shturmanʺ d. pl. Ivanovskīĭ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : Морское министерство, Главное гидрографическое управленіе, 1914)
Depth shown by soundings.; Title translation: Northern part of the Sea of Okhotsk from Okhotsk to Cape Aregichinsky according to the survey of the Hydrographic Expedition of the Eastern Ocean from 1908 to 1914.; Greenwich meridian.; "Masshtabʺ 1/750484 ili 8696 s. (10 milʹ) vʺ di︠u︡ĭmi︠e︡ po paralleli 58° 30' " = Scale 1/750484 or 8696 fathoms (10 miles) in 1 inch on the 58° 30' parallel.; "#319" -- bottom right margin; Gift from publisher Grayscale; 1:750,484